ULTRASONOGRAPHIC ASSESSMENT OF DIAPHRAGMATIC PARAMETERS FOR PREDICTING WEANING OUTCOME IN PATIENTS ON MECHANICAL VENTILATION IN THE ICU SETTING - Dr. Sakshi Khandelwal; Dr. Vandana Talwar; Dr. Pratibha Mudgal; Dr. Rohan Khandelwal; Dr. Ankush Garg; Dr. Bharani kumar B (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
A great number of critically ill patients require mechanical ventilation as a part of their care. Nevertheless, mechanical ventilation or the underlying ailment can lead to diaphragmatic dysfunction, a condition that may contribute to weaning failure. Extended time on the ventilator greatly increases patient morbidity and mortality. Symptoms and signs of muscle disease in ICU patient are often difficult to evaluate because of concomitant confounding factors. In recent times, the use of ultrasound has risen as a simple, non-invasive method for quantification of diaphragmatic excursion and contractile activity. MATERIAL AND MEHTODSThe study was conducted in the Department of Anaesthesia and Intensive care. This cohort study was conducted on 50 adult patients of either sex, admitted in Intensive Care Unit and scheduled to undergo extubation. The patient’s readiness to wean was assessed by clinical judgment. When the patient was ready to be weaned, he/she was put on pressure support ventilation (PSV). The pressure support was gradually reduced to 6cm H2O. If the patient remained stable and extubation was planned, T-piece trial was given. Baseline parameters (Heart rate, non-invasive blood pressure, respiratory rate, tidal volume, RSBI, SpO2, signs of respiratory distress- nasal flaring, sweating, agitation, use of accessory muscles, ABG analysis, Maximum Inspiratory Pressure (MIP), Maximum Expiratory Pressure (MEP) were recorded. Diaphragmatic excursion (DE) and diaphragmatic thickness fraction (DTF) were assessed ultrasonographically and diaphragmatic RSBI was later calculated.